Case Report: Efficacy of preoperative conversion therapy with lenvatinib, toripalimab, and hepatic arterial infusion chemotherapy in an advanced hepatocellular carcinoma - Mao, Jing; Zhang, Hengzhi; Yang, Xingxia; Yao, Yanjun; Sun, Xu; Yan, Qiang (Frontiers in Oncology, 2025)
Advanced hepatocellular carcinoma (HCC) has a poor prognosis. Conversion therapy based on non-surgical local therapy and drug therapy is an effective treatment for unresectable HCC. We report a case of HCC with intrahepatic metastasis and multiple venous tumor thrombi. After nearly 4 months of conversion therapy with lenvatinib, toripalimab combined with hepatic arterial infusion chemotherapy (HAIC), the lesions were significantly reduced, the portal vein tumor thrombus resolved, and the alpha-fetoprotein (AFP) decreased to the normal range. This patient had no serious adverse events during treatment. After a comprehensive assessment of the patient’s status, the patient eventually underwent curative surgical resection of the tumor and had a complete response. The successful experience of this case indicates that lenvatinib, toripalimab combined with HAIC has a good prospect as a conversion therapy for HCC with intrahepatic metastasis and multiple venous tumor thrombi.